EDUCATION ON HUMAN RIGHTS IN CHILDHOOD EDUCATION: WORKING WITH AFRICAN TALES - Klein, Ana Maria [UNESP]; Passos, Luana [UNESP]; Galindo, Monica Abrantes [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2018)
This article discusses the Human Rights Education (HRE) in kindergarten through the report of a project on African tales performed with students of early childhood education in the municipal town of northwestern Sao Paulo. The HRE became mandatory at all levels and parents education arrangements in 2012 with the National Guidelines for Human Rights Education and involves issues that relate to human dignity. Recognition and appreciation of diversity among people is one of its foundations. The project aims to answer the question of how to bring HRE into the schools and aimed to present and value aspects of African culture through literature readings were held discussions with children about their understanding of short stories and graphic records through drawings. The results of the activities show that children increased their concepts about fairies, queens and princesses, transcending Eurocentric conceptions.
Keywords: human rights; cultural diversity; African tales; childhood education